Flight guidance control using genetic algorithm combined with singular perturbation technique - Zhen-Qiang Qi; Guang-Da Hu; Zhao-Hua Yang; Fu-En Zhang (Proceedings of the 2003 International Conference on Machine Learning and Cybernetics (IEEE Cat. No.03EX693), 2003)
An advanced midcourse guidance law based on genetic algorithm (GA) and singular perturbation technique (SPT) is proposed in this paper. The proposed midcourse guidance formulation minimizes the flight time and maximizes terminal energy subject to a terminal intercept condition. GA is used to search the optimal attack angle for the flight trajectory, and SPT is applied to approximate the terminal flight time. By combining GA and SPT, the optimal flight guidance law is obtained consequently. Meanwhile, the paper completely eliminates the need for solving two-point boundary-value problems (TBPVP), which is too complex for derivation and implementation. The simulation results show that the resulting guidance law is near-optimal and the proposed method is valid.